1989
DOI: 10.1161/01.res.65.6.1718
|View full text |Cite
|
Sign up to set email alerts
|

Outward potassium currents in freshly isolated smooth muscle cell of dog coronary arteries.

Abstract: Outward membrane currents were characterized in single coronary smooth muscle cells of adult beagle dogs. The cells averaged 96.4 x 7.1 microns and had a resting potential of -50.7 mV, an input resistance of 307.9 M omega, a capacitance of 32.3 pF, and a calculated membrane surface area of 4,037 microns2. The cells contracted in response to external application of acetylcholine or high K+. In voltage clamp by use of the suction pipette method, outward current began to appear at -50 mV and reached 15.2 nA at 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
5
13
0
Order By: Relevance
“…Our records are consistent with pre- vious studies performed in guinea pigs, humans, rabbits (35), and rats (23). Most studies related to the characterization of membrane currents in coronary smooth muscle cells were performed on cells isolated from the LCA (8,21,26,35,37). In the present study, macroscopic outward currents were comparatively measured in myocytes from both LCA and RCA, and for the first time, we reported that macroscopic outward current elicited by membrane depolarization were greater in RCA cells than in LCA cells (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our records are consistent with pre- vious studies performed in guinea pigs, humans, rabbits (35), and rats (23). Most studies related to the characterization of membrane currents in coronary smooth muscle cells were performed on cells isolated from the LCA (8,21,26,35,37). In the present study, macroscopic outward currents were comparatively measured in myocytes from both LCA and RCA, and for the first time, we reported that macroscopic outward current elicited by membrane depolarization were greater in RCA cells than in LCA cells (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It is noteworthy that different types of K ϩ channels have been described in coronary myocytes from several animal models (8,22,23,35,37), supporting that coronary vascular tone may reflect the integrated contribution of a diverse population of K ϩ channels. Nevertheless, to the best of our knowledge no study has so far compared the contribution of the K ϩ channels in both LCA and RCA from the same species.…”
mentioning
confidence: 89%
“…In these experiments, outward currents were elicited by a 600 msec voltage depolarizing step from -90 mV to +70 mV, followed by a 500 msec pulse to more "],,, these potentials were more positive than those predicted by the Nemst equation, 14 as has been noted previously. 15 However, the slopes of the plots were -58.5 (WKY), -56.2 (SHR), -56.5 (DS), and -54.3 (PS), similar to the slope of -5 8 predicted for a purely K + -selective channel by the Nernst equation.…”
Section: Comparison Of K + Currentssupporting
confidence: 68%
“…Most other procedures employ mixtures of collagenase with other enzymes in Ca2"-free solutions (e.g. Bolton et al 1985;Inoue et al 1985;Wilde & Lee, 1989). The protocols are time consuming, taking up to 2 h and often requiring several incubations in enzyme.…”
Section: Cell Isolation Proceduresmentioning
confidence: 99%
“…However, the physiological relevance of this type of current is not yet clear. More recently, a quasiinstantaneous, time-independent K+ current has been reported in rabbit portal vein (Hume & Leblanc, 1989) and in dog coronary artery (Wilde & Lee, 1989), which might play a role in maintaining the resting membrane potential. This paper describes a new and convenient method for isolating cells and characterizes the major outward currents in rabbit pulmonary artery.…”
Section: Introductionmentioning
confidence: 99%